Main Duties Implementation Supervisors of SMK Negeri Kepulauan Mentawai - Foniaman Zebua; Sufyarma Marsidin; Rifma Rifma (Fakultas Ilmu Pendidikan UNP)
The purpose of this research is to describe about the implementation of the principal task of supervisors at SMK Negeri Kabupaten Kepulauan Mentawai has been implemented optimally, the process of performing the main duties of supervisors in SMK in Mentawai Islands District in the field of academic and managerial areas in accordance with predetermined programs, and obstacles faced by supervisors SMK Negeri in district Islands Mentawai in the execution of tasks in the field. The results of this study are as follows: (1) the implementation of the main task of supervisors has not been implemented optimally, 2) the process of carrying out the main task of supervisor regency in the academic field and managerial field is not in accordance with the program that has been determined and (3) there are constraints faced by school supervisors in carrying out their main tasks such as transportation and communication constraints.